Ծիսական առարկաների հինհայերէնեան անուանումները՝ որպէս արդի հայերէնի բառային կազմի հարստացման աղբիւր - Կարապետեան, Սիրարփի (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Целью данной статьи является изучение слов, характеризующих ритуальные предметы, для которых мы посчитали необходимым выделить названия и термины церковных принадлежностей. Мы изучили 27 терминов, обозначающих ритуальные предметы, названия которых составляют часть религиозно-церковного слоя армянской лексики. Многие слова и термины, относящиеся к этому слою, относятся к дописьменному периоду, записаны начиная с V века, часть из которых в ходе исторического развития претерпела различные семантические изменения. Обрядовые термины мы сочли целесообразным интерпретировать с этимологической и семантической точек зрения, что позволило точно разделить и объяснить их. Церковные термины занимают зна- чительное место в лексике армянского языка, и их изучение представляет ценность как с синхронной, так и периодической точек зрения. The purpose of the given article is to study the words characterizing ritual objects, for which we considered it necessary to highlight the names and terms of church accessories. We have studied 27 terms denoting ritual objects, the names of which are part of the religious-ecclesiastical layer of the Armenian vocabulary. Many words and terms related to this layer and belonging to the pre-literate period have been recorded since the 5th century; some of them have undergone various semantic changes in the course of the historical development of the language. We considered it expedient to interpret ritual terms from etymological and semantic points of view, which made it possible to accurately separate and explain them. Church terms have a significant place in the vocabulary of the Armenian language, and their study is valuable both from synchronic and diachronic points of view.
Keywords: Բանասիրութիւն